Role of Oxidative Stress, Methionine Oxidation and Methionine Sulfoxide Reductases (MSR) in Alzheimer's Disease - Sanjana Chandran; David Binninger (MDPI AG, 2023)
A major contributor to dementia seen in aging is Alzheimer's disease (AD). Amyloid beta (Aβ), a main component of senile plaques (SPs) in AD, induces neuronal death through damage to cellular organelles and structures, caused by oxidation of important molecules such as proteins by reactive oxygen species (ROS). Hyperphosphorylation and accumulation of the protein tau in the microtubules within the brain also promote ROS production. Methionine, a residue of proteins, is particularly sensitive to oxidation by ROS. One of the enzyme systems that reverses the oxidative damage in mammalian cells is the enzyme system known as Methionine Sulfoxide Reductases (MSRs). The components of the MSR system, namely MSRA and MSRB, reduce oxidized forms of methionine (Met-(o)) in proteins back to methionine (Met). Furthermore, the MSRs scavenge ROS by allowing methionine residues in proteins to utilize their antioxidant properties. This review aims to improve the understanding of the role of the MSR system of enzymes in reducing cellular oxidative damage and AD pathogenesis, which may contribute to effective therapeutic approaches for AD by targeting the MSR system.